Dismiss Notice
Join Physics Forums Today!
The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

Homework Help: Log proof

  1. May 20, 2007 #1

    i can do the addition and subtraction rules no problem, but for some reason i'm stuggling with this one,
    just point me in the right direction, or help with the whole thing i'm not bothered, i just hope it aint in my exam tomorrow lol
  2. jcsd
  3. May 20, 2007 #2


    User Avatar
    Staff Emeritus
    Science Advisor

    Well, one way of doing it is to write log(x^k) as log(x.x.x...x) [where there are k x's in the argument of the logarithm]. Then invoke the rule log(ab)=log(a)+log(b). Of course this only works for positive integers!

    A better proof is to let y=log_a(x), so that a^y=x. Then x^k=(a^y)^k=a^(yk). Hence, log_a(x^k)=ky=k log_a(x).
  4. May 20, 2007 #3
    but to get from x^k = a^(yk)
    to log_a(x^k) = ky

    you would need to go via the rule i'm trying to prove
    ie log_a(x^k) = log_a(a^ky) = ky log_a(a) = 1ky
    so i didnt know if that was a feasible move
  5. Feb 17, 2009 #4
    No, you do not have to use the log rule that you are trying to prove to continue...

    You want to prove: loga xk = k loga x


    (1) First, let y = loga x

    (2) Rewite (1) in exponential form using anti-log: ay = x

    (3) Next, add exponent k to both side and we have: ayk = xk

    (4) Now you "log" both side to have: loga ayk = loga xk

    (by logging both side you do not use the log rule you are trying to prove)​

    (5) but we know the log rule said: logaayk = yk

    (6) so (4) becomes: yk = loga xk

    (7) but (1) said y = loga x

    (8) so (6) becomes (loga x ) (k) = loga xk

    (9) Re-arrange the left, we have: k loga x = loga xk

    (10) Proof complete QED
Share this great discussion with others via Reddit, Google+, Twitter, or Facebook